A structure-activity relationship analysis of anthraquinones with antifouling activity against marine biofilm-forming bacteria - Preet, Gagan; Gomez-Banderas, Jessica; Ebel, Rainer; Jaspars, Marcel (Frontiers in Natural Products, 2022)
Anthraquinones (AQs) are chemical scaffolds that have been used both naturally and synthetically for centuries in the food, pharmaceutical, cosmetic and paint industries. AQs, such as citreorosein and emodin, are common additives in antifouling paints which help prevent the global issue of biofouling. To determine the antifouling potential of a family of structurally related compounds nineteen twenty AQs (1-1920), were tested for their microbial growth and biofilm adhesion inhibition activity against three marine biofilm forming bacteria, Vibrio carchariae, Pseudoalteromonas elyakovii and Shewanella putrefaciens. More than three quarters of the tested AQ compounds exhibited activity against both V. carchariae and P. elyakovii at 10 μg/mL whilst exhibiting low antimicrobial effects. The most active compounds (1, 5, 6, 7, 9, 10, 14, 15, 18, 19, 20) were tested for their minimum inhibitory concentrations (MICs) which highlighted that all the tested compounds were highly effective at inhibiting the biofilm growth of P. elyakovii at a very low concentration of 0.001 μg/ml. The variability in MIC for inhibiting the biofilm growth of V. carchariae was assessed by analysing the structure-activity relationships (SARs) between the AQ compounds, and the key structural features leading to improved biofilm growth inhibition activity are reported. Molecular docking analysis was also performed to assess whether interruption of quorum sensing (QS) in V. carchariae could be a possible mode of action for the antifouling activity observed.